2007
DOI: 10.1515/cclm.2007.294
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic usefulness of a third-generation anti-cyclic citrulline antibody test in patients with recent-onset polyarthritis

Abstract: Testing with both types of anti-CCP kit is highly specific for the presence of RA. In our ROP group, anti-CCP2 and anti-CCP3 exhibited similar diagnostic efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 2 publications
0
12
0
1
Order By: Relevance
“…We identified 797 articles, of which 17 met the inclusion criteria [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. There were 1952 RA patients selected from Europe, Americas and Asia in the remaining 17 articles that were eventually available for this meta-analysis (see Table 1).…”
Section: Search Results and Characteristics Of The Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified 797 articles, of which 17 met the inclusion criteria [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. There were 1952 RA patients selected from Europe, Americas and Asia in the remaining 17 articles that were eventually available for this meta-analysis (see Table 1).…”
Section: Search Results and Characteristics Of The Studiesmentioning
confidence: 99%
“…We reviewed the quality of the included articles that are of high level in terms of QUADAS rating. However, items 10 and 11 (index test results blinded and reference standard blinded to index test) of all studies except for one article [27] are "unclear". The two antibodies in eight articles [26, 27, 29, 32-34, 37, 38] were not described in detail, so they did not reach item 8 (adequate index test description).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At this time it is difficult to interpret the additional value provided by anti-CCP3, except that it is most likely equivalent to anti-CCP2 in terms of overall sensitivity and specificity for RA 20,21,22 . In our study, the difference in sensitivity and specificity between the 2 tests was not statistically significant, although consistently more specimens were anti-CCP3+ than anti-CCP2+ (Table 1) in both the RA and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been well documented and widely reported that about one-third of RF-RA patients are anti-CCP2+ 19 . Recently, another synthetic citrullinated peptide, CCP3, has been utilized as antigen in a third-generation assay and has been shown to have similar sensitivity and specificity to CCP2 for RA 20,21,22 . However, the relationships among anti-CCP2, anti-CCP3, and rheumatoid factors has not yet been investigated.…”
Section: Rheumatologymentioning
confidence: 99%